Reactional state in an atypical borderline tuberculoid leprosy: a spectrum of type 2 leprosy reaction? - Felipe Marinho Rocha de Macêdo (2025)
Leprosy is a chronic granulomatous neurocutaneous disease with a wide clinical, histopathological, and immunological spectrum. Leprosy reactions can occur at any stage of the disease, even in untreated individuals, reflecting abrupt immunological shifts. This report describes a case of an otherwise healthy female patient referred to the dermatology outpatient service due to an isolated, asymptomatic, long-standing single lesion on her left thigh for five years. A diagnosis of borderline tuberculoid (BT) leprosy was made. Within 30 days, the patient complained of a sudden onset of systemic symptoms and showed multiple hemorrhagic bullae on her lower limbs, prompting suspicion of an atypical type 2 leprosy reaction. BT leprosy is typically characterized by a few scattered infiltrated plaques with asymmetrical and irregular nerve thickening. Histopathology often shows granulomas composed of epithelioid cells and an admixture of macrophages and lymphocytes. Type 2 leprosy reactions usually manifest as painful erythematous papules, plaques, and nodules. Although several type 2 reaction patterns have been described in literature, diagnosis remains challenging.